INITIAL GEOMETRIC IMPERFECTIONS AKIBAT TEKUK SINGLE CURVATURE MOMENT PADA BALOK BAJA SEDERHANA - Erlina Yanuarini; Yanuar Setiawan; Tri Widya Swastika (Construction and Material Journal, 2020)
Steel beams are susceptible to initial geometric imperfections due to improper fabrication and installation processes. Consequently, long steel beams without stiffening are prone to bending due to lateral torsion. The purpose of this study is to determine the effect of variations in the initial geometric imperfections of Single Curvature-Moment (SCM) on the moment, total displacement, displacement in the X direction (U1), displacement in the Y direction (U2), and twist. This study used an RH profile with a compact flange and web. The boundary condition used is a simple beam with an initial geometric imperfection due to single moment-curvature (SCM) bending. The variations used are the initial geometric imperfections values of SCM 0 mm (without initial geometric imperfections), SR5 (with initial geometric imperfections of 5 mm), and SR10 (with initial geometric imperfections of 10 mm). Initial geometric imperfections of SCM in steel beam decreased moment capacities up to more than 2% in elastic conditions and 12% in plastic states. This SR10 beam is also a beam that has a displacement of the X-axis (U1 = -203,960 mm), a displacement of the Y-axis (U2 = -255,615 mm), and the most significant twist (28,179 °). Keywords: Buckle, Initial Geometric Imperfections, Single Curvature-Moment.